The Right Man in the Right Job: Evaluation of Employee Placement Policy in South Tangerang City - Renny Anggarani Nur Prasasti; Rahmat Salam; Izzatusholekha (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study aims to determine the evaluation of employee placement policies in South Tangerang City. The method used in this study is a qualitative method with a descriptive approach which is collected through documentation, observation, and interview methods. The results of this study indicate that this policy succeeded in achieving the expected results. Several Mayor Regulations have been issued to regulate the placement of employees, so that there is a clear legal basis in South Tangerang City. Efforts such as employee assessment and merit application design programs have made staffing more efficient, helping to apply the principle of "the right person in the right position" more effectively, therefore this policy has sufficient alternatives and is able to solve problems, but still has problems which is still influenced by the political element in policy making.